PERBEDAAN KADAR GLISEROL, ESTER, MONO- DAN DIGLISERIDA PADA VARIASI PERLAKUAN REFINED BLEACHED DEODORIZED PALM OIL - Mauli Anshori; Zakwan; Rahimah (Institut Teknologi Sawit Indonesia (ITSI), 2020)
The Refined Bleached Deodorized Palm Oil (RBDPO) is a derived product of crude palm oil that has twofraction (olein and stearin) in ambient temperature. This research aim to analyze the variation of treatmenton the RBDPO. The design of research was non-factorial completely randomized with three variable oftreatment such the RBDPO with glycerol (A), the RBDPO (B) and the RBDPO with lipase enzyme. Theconcentration of glycerol, ester, mono- and diglyceride was tested by Gas Chromatography method. The datawere analyzed by using descriptive method with boxplot and histogram. The result showed that the highestconcentration of glycerol; ester; mono- and diglyceride respectively were showed in treatment B (1,5922%);C (9,5699%); C (0,1783%); C (3,3329). The boxplot graphic described the differences among the treatmentthat the RBDPO with lipase enzyme had the most extensive concentration of glycerol, ester, mono- anddiglyceride.